A study of tunnel stability with special reference to the effect of the stress field environment - Chen, Hui (1992)
The thesis is a study of the stability, closure behaviour and rock fracture development associated with mine tunnels with particular reference to Coal Measures conditions. A detailed survey has been carried out of relevant theories and mathematical concepts which relate to tunnel stability and the effects of in situ stresses. Of special importance has been identifying appropriate mathematical theories which relate to the field of scholarship undertaken. The literature survey has found useful application especially in giving guidance on those areas needing further investigation. The author discusses mathematical theories in relation to the research undertaken.